PELATIHAN PEMBUATAN BAKSO RUMPUT LAUT SEBAGAI INOVASI PENINGKATAN PRODUKSI OLAHAN PANGAN DI PANTAI OESAPA - Saraswati, Suprabadevi; Tallo, Ismawan; Huky, Rut Kristiani (Jurnal Pengabdian Perikanan Indonesia, 2022)
Seaweed is one of the most valuable aquaculture commodities to be developed. The content of alginate, carrageenan and agar makes seaweed the main ingredient in the manufacture of foodstuffs, beauty and other industries. In its development, seaweed processing is growing, especially in the culinary field. Seaweed meatballs are made from a mixture of meat and seaweed, without flavoring and food coloring, so they have a high nutritional content and are safe for consumption. Training on making seaweed meatballs was deemed necessary at Warna Oesapa Beach to process the abundant seaweed production in NTT. The training is carried out in stages starting from the preparation stage, implementation stage, and evaluation stage. The training was held at Color Oesapa Beach, Oesapa Village, Kupang City and was attended by 30 participants. The manufacture of products is carried out according to a predetermined recipe. The result of the training on making seaweed meatballs is that people in Oesapa Village are expected to be able to take advantage of the seaweed harvest so that they can improve their welfare and independence in entrepreneurship. This activity has never been carried out before, so it received a good response from the residents and the village head at Color Oesapa Beach. The training activities for making seaweed meatballs were finally able to be applied properly so that they were able to help the family's economic condition and increase the value of the welfare of the community at Warna Oesapa Beach.